Senyawa Bioaktif KANDUNGAN SENYAWA BIOAKTIF KULIT JENGKOL (ARCHIDENDRON JIRINGA) DENGAN PERBEDAAN KONSENTRASI PELARUT ETANOL SEBAGAI POTENSI FEED ADDITIVE TERNAK RUMINANSIA: KANDUNGAN SENYAWA BIOAKTIF KULIT JENGKOL MENGGUNAKAN PERBEDAAN KONSENTRASI PELARUT ETANOL - Purnama Ningrum, Ningrum; Hartati, Lilis; Suhendra, Danes; Hidayah, Nur; Rahayu, Tri Puji (Jurnal Peternakan Nusantara, 2024)
This study was aimed to determine the content of bioactive compounds in jengkol peel (Archidendron Jiringa) with different concentrations of ethanol as a potential feed additive for ruminants. The material used in this study was 50g jengkol peel flour in each treatment. The research method used was an experimental trial using a Completely Randomized Design (RAL) with 5 treatments and 4 replications. The treatments used were P1 (100% aquadest), P2 (24% ethanol (75% aquadest + 25% ethanol)), P3 (48% ethanol (50% aquadest + 50% ethanol)), P4 (72% ethanol (25% aquadest + 75% ethanol)), and P5 (96% ethanol (100% ethanol)). The parameters observed in this study were tannin content, saponin, flavonoid, and total phenol. The data obtained were analyzed using Analysis of Variance (ANOVA), then if there were significantly differences, Duncan Multiple Range Test (DMRT) was carried out. The results of the study of jengkol peel extract using ethanol solvents with different concentrations gave significantly different results of tannin and saponin content (P<0.05), while the flavonoid content and total phenol were not significantly different (P>0.05). Based on the research conducted, it is concluded that jengkol peel extract has the potential as a feed additive for ruminants, as evidenced by the results of the tannin content of 8,22% and the saponin content of 13,47% with an ethanol concentration of 48%, but did not affect the flavonoid content and total phenol extracted from jengkol peel (Archidendron jiringa).